Surgical Management of Urolithiasis in a Male Labrador: A Case Report - Ghosh, Chhotan Kumar; Roy, Subhasis; Sarkar, Pradip; Singh, Anil (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Urinary stones (urolithiasis) are a common condition responsible for lower urinary tract disease in dogs. The formation of calculi is associated with precipitation and crystal formation of a variety of minerals. Urinary calculi can damage the lining of the urinary tract, causing inflammation, which may predispose to bacterial infection. If calculi become lodged in the ureter, causing an obstruction, it may result in serious kidney damage. Unilateral ureteral obstruction may result in hydronephrosis with loss of function of the kidney. Urine retention may rupture the bladder with distension of the renal capsule (Tion et al., 2015 and Mudasir et al., 2018). So, an urgent cystotomy for removal of uroliths is the most commonly performed surgical procedure to save the life of the pets.